MATHEMATICS SS 1 SECOND TERM WEEK 3
Topic: GENERAL FORM OF QUADRATIC EQUATION LEADING TO FORMULA METHOD.
Quadratic equation refers to polynomial equation that have a general form of ax2+bx+c=0, where a, b and c are co-efficient. a≠0 otherwise it would be a linear equation and c is constant. The quadratic formula is defined as x= (-b±√b2-4ac)/2a, where “a” is the co-efficient of the x2, b is the linear co-efficient of the x and c is the constant term. Therefore, the quadratic formula involves substituting the co-efficient from a given quadratic equation into the formula.
Derivation of the quadratic formula.
For all quadratic equations, we have the general form:
ax2 + bx + c = 0
1. Moving the “non x” to the right,
we get: ax2 + bx = – c
2. Dividing by ‘a’ (the coefficient of x2),
we get: x2 + bx/a = – c/a
3. We take the coefficient of x, divide it by 2, square the result and then add that to both sides of the equation. The coefficient of x is b/a, one half of that is (b/2a) and squaring that,
we get b2/4a2.
Adding that both sides of the equation,
we have x2 + bx/a + b2/4a2 = – c/a + b2/4a2
4. Taking the square roots of both sides,
we get: x + b/2a = -c/a + b2/4a2
Moving b/2a to the right ,
Simplifying x =-b/2a±b2-4ac/2a
Questions:
Solve for the roots for the general form of quadratic equation
1. 4x2 – 5x + 1 = 0
A. x = 1, ¼ B. x = -1, ¼ C. 1, 1 D. 1/4, 1
2. 2x2 – 14x – 13 = 0
A. 5+53/2, 7+53/2 B. 7+53/2, 5+53/2 C. 7+53/2, 7-53/2 D. 7+56/2, 7+3/2
3. 3x2 + x – 2 = 0
A. x = 2/3, -1 B. x = -2/3, 1 C. x = -2/3, -1 D. x = -2/3, 1
4. 3×2+4x+1=0
A. x =-1, -1/3 B. x = 1, -1/3 C. x=-1, 1/3 D. x=1, 1/3
5. 2x2 – 3x – 6
A. ¾, 4/9 B. ¾, -9/4 C. 9/4, ¾ D. 9/5, ¾
Answers
1. A 2. C 3. C 4. A 5. B